Neurological Complications and Noninvasive Multimodal Neuromonitoring in Critically Ill Mechanically Ventilated COVID-19 Patients - Battaglini, Denise; Santori, Gregorio; Chandraptham, Karthikka; Iannuzzi, Francesca; Bastianello, Matilde; Tarantino, Fabio; Ball, Lorenzo; Giacobbe, Daniele Roberto; Vena, Antonio; Bassetti, Matteo; Inglese, Matilde; Uccelli, Antonio; et al. (Frontiers in Neurology, 2020)
Purpose: The incidence and clinical presentation of neurological manifestations of coronavirus disease-2019 (COVID-19) remain unclear. No data regarding the use of neuromonitoring tools in this group of patients are available. Methods: This is a retrospective study of prospectively collected data. The primary aim was to assess the incidence and type of neurological complications in critically ill COVID-19 patients and their effect on survival, as well as on hospital and intensive care unit (ICU) length-of-stay. The secondary aim was to describe cerebral hemodynamic changes detected by noninvasive neuromonitoring modalities such as transcranial doppler (TCD), optic nerve sheath diameter (ONSD), and pupillometry. Results: Ninety-four patients with COVID-19 admitted to an ICU from February 28 to June 30, 2020, were included in this study. Fifty-three patients underwent noninvasive neuromonitoring. Neurological complications were detected in 50% of patients, with delirium as the most common manifestation. Patients with neurological complications, compared to those without, had longer hospital (36.8±25.1 vs. 19.4±16.9 days, p<0.001) and ICU (31.5±22.6 vs. 11.5±10.1 days, p <0.001)-stay. The duration of mechanical ventilation was independently associated with risk of developing neurological complications (OR 1.100, 95%CI 1.046-1.175, p=0.001). Patients with increased intracranial pressure measured by ONSD (19% of the overall population) had longer ICU-stays. Conclusions: In conclusion, neurological complications are common in critically ill patients with COVID-19 receiving invasive mechanical ventilation and are associated with prolonged ICU length-of-stay. Multimodal noninvasive neuromonitoring systems are useful tools for early detection of cerebrovascular changes in COVID-19.